Designing home-based physical activity programs for rural cancer survivors: A survey of technology access and preferences - Salerno, Elizabeth A.; Gao, Rohana; Fanning, Jason; Gothe, Neha P.; Peterson, Lindsay L.; Anbari, Allison B.; Kepper, Maura M.; Luo, Jingqin; James, Aimee S.; McAuley, Edward; Colditz, Graham A. (Frontiers in Oncology, 2023)
Background: While technology advances have increased the popularity of remote interventions in underserved and rural cancer communities, less is understood about technology access and preferences for home-based physical activity programs in this cancer survivor population. Purpose: To determine access, preferences, and needs, for a home-based physical activity program in rural cancer survivors. Methods: A Qualtrics Research Panel was recruited to survey adults with cancer across the United States. Participants self-reported demographics, cancer characteristics, technology access and usage, and preferences for a home-based physical activity program. The Godin Leisure Time Exercise Questionnaire (GLTEQ) assessed current levels of physical activity. Descriptive statistics included means and standard deviations for continuous variables, and frequencies for categorical variables. Independent samples t-tests explored differences between rural and non-rural participants. Results: Participants (N=298; mean age=55.2±16.5) had a history of cancer (mean age at diagnosis=46.5), with the most commonly reported cancer type being breast (25.5%), followed by prostate (16.1%). 74.2% resided in rural hometowns. 95% of participants reported accessing the internet daily. On a scale of 0-100, computer/laptop (M=63.4) and mobile phone (M=54.6) were the most preferred delivery modes for a home-based physical activity intervention, and most participants preferred balance/flexibility (72.2%) and aerobic (53.9%) exercises. Desired intervention elements included a frequency of 2-3 times a week (53.5%) for at least 20 minutes (75.7%). While there were notable rural disparities present (e.g., older age at diagnosis, lower levels of education; ps<.001), no differences emerged for technology access or environmental barriers (ps>.08). However, bias due to electronic delivery of the survey should not be discounted. Conclusion: These findings provide insights into the preferred physical activity intervention (e.g., computer delivery, balance/flexibility exercises) in rural cancer survivors, while highlighting the need for personalization. Future efforts should consider these preferences when designing and delivering home-based interventions in this population.